The effect of physical exercise of different intensities on the mental health of college students - Rong Du; Fei Zhang; Miao Chang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
To investigate the impact of different intensities of physical activity on college students' mental health and fortitude. For a freshman in high school, the psychological state Experimentally, the effects of various exercise methods on various psychological issues were explored. It transpires that: Exercise benefits the heart. The rational state regulates effectively. Taijiquan is vital in learning anxiety; The healthy body is held, tai chi, and feather hairball has a noticeable improvement in symptoms with tai chi. The author employs cluster sampling, selects a college student as the research object, and employs the SCL-90 self-assessment scale and the adolescent mental toughness scale to examine the effect of physical exercise of varying intensities on improving the mental health and mental toughness of college students. •To a first-year high school student 786 To perform a questionnaire survey. Written by Zhou Bucheng et al., the Mental Health Diagnostic Test (M IT I) was used to conduct the survey. 753 recoveries, 3 valid surveys, and 384 boys. There were 27 men and 9 women in total. Input the original data acquired from the questionnaire with XE C king:12 X(commit to the actual number into the computer. The co-printed names were examined for physical symptoms using the M H T scale. We were learning about anxiety and psychological allergy tendencies for the freshman. According to the ex E E Zl X(random sampling), Each group contributes functions, which are arranged in basketball, setting-up exercise, tai chi, and feather hair. The experiment was conducted in four separate groups—the eight-week interval between exercising twice weekly and working out. The Fording exam was administered eight weeks later compared to the previous period. The scores of somatization, compulsion, interpersonal sensitivity, depression, anxiety, and paranoia on the SCL-90 scale of college students in the observation group were significantly lower than those in the control groups 1, 2, and 3. All P values were < 0.01; The scores of the psychological toughness questionnaire in the observation group were significantly lower than those in the control groups 1 and 2. Both P values were 0.01; Students in the observation group believed physical activity might positively affect social interaction, spiritual emancipation, and self-discipline. • Students with learning anxiety performed minimal Tai Chi exercises. There were statistically significant differences between groups (P & LT; 0.05), indicating that only Taiji boxing is of concern. This may be a requirement of "To Harbin" tai chi to enhance the impact. "The mind controls the action." Under the control of awareness, the neurological system is always fully set in the precision of every action, whether false or true, opening and closing, coordinating - and even to Garden life, metamorphosis, and respiration. Be determined to accomplish Flexibility and equilibrium of the neurological system are enhanced further. Self-ideation management Additionally, the control ability improves anxiety symptoms such as hypersensitivity. The heart does not experience real fear without cause. Anxiety and dread prevent the mind from being controlled, preventing the exercise of self-control and the section. The observation group's somatization, compulsion, interpersonal sensitivity, sadness, anxiety, and paranoid scores were considerably higher than those of the control groups 1, 2, and 3 (P < 0.01). The scores on the psychological resilience scale were substantially higher in the observation group than in the control group 1,2, P < 0.01. The students in the observation group stated that physical exercise might positively affect social interaction, physical and mental health, mental emancipation, and self-training, and their scores were statistically significant (P < 0.05) when compared to those in the other groups. College students can improve their mental health and mental toughness through moderate-intensity physical activity, which merits attention.